Efficacy of Bihemispheric tDCS in Rehabilitation of Non-Fluent Aphasia: A Single-subject Pilot Study - Aydın, Dilara Gamze; Bulut, Talat; Karsan, Çağdaş (Clinical and experimental health sciences (Online), 2024)
Objective: Transcranial direct current stimulation (tDCS) has emerged as a potentially effective complementary tool in rehabilitation of aphasia. However, there is no consensus regarding the optimal tDCS montage to augment language outcomes in aphasia. Against this background, the present study aimed to examine efficacy of tDCS combined with language therapy in aphasia rehabilitation and to compare two different montages. Methods: A right-handed participant suffering from chronic, non-fluent aphasia following stroke affecting the left hemisphere underwent a 5-week procedure involving tDCS coupled with language therapy. The procedure comprised two 5-day treatments of bihemispheric tDCS (over inferior frontal and posterior temporal sites determined using the international 10-20 EEG system). As part of both treatments, the left hemispheric targets were excited through anodal tDCS while simultaneously inhibiting their right-hemispheric homologues through cathodal tDCS. Baseline, post-treatment and follow-up assessments were obtained using a comprehensive language assessment tool. Results: An increase in language outcomes, particularly in repetition, was observed following the treatments. It was also found that therapy gains were more robust following bihemispheric stimulation of the posterior temporal sites compared to the inferior frontal targets. Conclusion: Bihemispheric tDCS coupled with language therapy appears to be effective in remediating language symptoms, particularly in terms of the repetition ability, in aphasia.